Penggunaan Media PAJS untuk Mengembangkan Kecerdasan Matematis dan Interpersonal Peserta Didik dalam Pembelajaran Matematika Materi Skala - Hardani Hardani (Idealmathedu: Indonesian Digital Journal of Mathematics and Education, 2019)
This study aims to determine the improvement of the development of mathematical and interpersonal intelligence of students in learning mathematics of scale material using the actual Sifter Board media. This research is a development research used to develop mathematics learning media in the sixth grade of the UPTD Tambegan Elementary School. Learning outcomes that were carried out previously showed no development of students' mathematical and interpersonal intelligence. After the learning with PAS media was carried out, students were not only able to work on material scale questions, but with the material acquisition activities they were able to make problems and do it correctly. In addition, the stages of using PAS media can develop the ability to work together, the ability to be confident, the ability to motivate others, mutual respect. Based on the results obtained it can be concluded that the use of PAJS media can improve students' mathematical and interpersonal intelligence.